The Bahay Biyaya Library of the Tahanang Walang Hagdanan a case study of the library in a rehabilitation agency - Perez, Marilou Grace B.; Gonzales, Grace Marie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This study determined whether the Bahay Biyaya library and the libraries of the respective schools of the student-residents of Bahay Biyaya are fulfilling its objective in serving its disabled clientele. Systems Plus College Foundation in Cubao, University of Santo Tomas and Trinity College of Quezon City were covered in this study. In addition, the Tahanang Walang Hagdanan in Cainta Rizal was also included in order to provide a concrete description of the information needs of the disabled persons. In the study, it was found that: (1) only Systems Plus College Foundation Library has excellent library services for physically disabled persons ; (2) the Bahay Biyaya library has poor library services for persons with disabilities. Its library needs further improvement;(3) most of the respondents were employees/workers, aged 26 to 46 years old;(4) there were only 10 (40) students surveyed from Bahay Biyaya and only one (2.32) was surveyed from Tahanang Walang Hagdanan ; (5) a total of 13 (52) orthopedically disabled respondents with paraplegia, skeletal and muscular dystropies were from Bahay Biyaya while, there were 43 (100) orthopedically disabled respondents from Tahanang Walang Hagdanan and ; (6) The respondents were classified as/to be classified as the fully/ partially productive group of persons with disabilities.
This study concludes that:(a) rehabilitation resource agencies covered in this study do not have services or any library specifically for persons with disabilities; (b) private academic libraries included in this study do no have services specifically for physically disabled persons because their libraries generally cater to "normal" or "able-bodied" individuals; (c) physically disabled persons will have difficulty in getting services from these libraries since there were constraints with regard to physical access, access to materials and services, media formats and special collection, services and communication with person to persons with disabilities; (d) the library collection, facilities and equipment of these libraries were still inadequate for persons with disabilities with respect to the needs related to the specialized needs/interests of the disabled clientele;(e) having a library which has sufficient materials, equipment, facilities and services were indeed important with regard to education and mainstreaming of physically disabled persons as productive individuals; (f) disabled persons were very receptive about having an improve or well-developed library programs and services for them;(g) The needs of the physically disabled persons from these rehabilitation resource agencies vary; (h) preferred subject areas, language preference and preferred type of types of library materials as well as recommendations of the physically disabled persons should be considered in the formulation of collection development policies for a library and; (i) fund/budget, physical structure of the library and types of library programs and services rendered should be given priority in order to provide satisfactory library services for persons with disabilities.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Bahay Biyaya Library; Libraries and people with disabilities -- Philippines -- Cainta, Rizal